The Influence of Firm Size, Capital Structure and Profitability on Firm Value in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange - Nurhandari, R.A. Lutfiah; Fatimah, Fatimah; Choiriyah, Choiriyah (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
This study aims to determine the effect of company size, capital structure and profitability on company value in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX). The samples used were 14 from 27 populations using a purposive sampling technique with a research period of 8 years, 2015-2022. The analysis technique used is multiple linear regression. The study results show that company size, capital structure and profitability significantly affect firm value in food and beverage companies on the Indonesia Stock Exchange. Partially, capital structure impacts a firm value; profitability significantly affects firm value, while firm size has no significant impact on firm value